Peranan Kepemimpinan Kepala Sekolah Dalam Meningkatkan Mutu Pendidikan Melalui Kurikulum Merdeka - Indri Fauzizah; Tiara Rahma Dona; Alan Pratama; Merika Setiawati; Nikmah Hayati (CV. ITTC INDONESIA, 2025)
This study aims to examine the role of school principals' leadership in improving the quality of education through the implementation of the Merdeka Curriculum. The Merdeka Curriculum provides flexibility for educational institutions to design learning that is more contextual, inclusive, and student-centered. As educational leaders, school principals play a crucial role in driving instructional innovation, strengthening human resources, and building strategic communication both with teachers and external stakeholders. This research employs a Systematic Literature Review (SLR) approach by analyzing peer-reviewed scholarly articles published between 2020 and 2024. Data were collected from reputable national and international journals accessed through databases such as Google Scholar, Semantic Scholar, and Garuda (Kemendikbud). The findings indicate that effective school leadership through strategies such as academic supervision, ongoing professional development, and collaboration in Profil Pelajar Pancasila (Pancasila Student Profile) projects can significantly enhance the quality of the learning process. With strategic and collaborative approaches, school principals serve as key agents in transforming education in the era of the Merdeka Curriculum.